In situ STM study of electrocrystallization of Ag on Ag(111) - García,Silvana G. (2004)
The electrocrystallization process was studied in the system Ag(111)/Ag+, SO4= by in situ scanning tunneling microscopy (STM). The results show that Ag deposition occurs preferentially at step edges following a layer-by-layer growth mechanism, but polarization and imaging conditions greatly affect the local kinetics of this process. At STM-tip potentials more positive than the Ag/Ag+ equilibrium potential, a local dissolution of the substrate underneath the tip is observed even at low negative substrate overpotentials, at which the overall substrate current density is cathodic. An in situ STM imaging of Ag deposition was possible at sufficiently high negative substrate overpotentials. An estimation of the local deposition current density, however, indicates that the deposition rate underneath the STM-tip is reduced. These results are explained by the presence of an electric field between the STM-tip and the substrate, which affects the potential distribution directly underneath the tip, producing a large shielding of the diffusive flux of Ag+ ions.